Influence of personality variable in student academic performance when they complete secondary education (ESO) and begin Baccalaureate - Muelas Plaza, Álvaro (Historia y Comunicación Social, 2014)
Academic performance is an issue for concern to students, parents, teachers and authorities, and not only in our country, in many other European countries and other continents. Scientific research has long been trying to clarify the key school performance and in recent years has substantially changed the traditional approach with which he had been working. Therefore, this article focuses on analyzing one of the variables that can influence the academic performance of students, as is personality.